Revisiting Cash Endowment and House Money Effects in an Experimental Auction of a Novel Agri‐food Product in the Philippines. Issue 2 (June 2014) - Depositario, Dinah Pura T.; Nayga, Rodolfo M.; Zhang, Yu Yvette; Mariano, Robert Dominick E.
<x xml:space="preserve">Abstract</x> This study explores the effect of varying cash endowments on bidding behavior in auction experiments conducted in a developing country. Our results suggest that cash endowment levels can have different effects on bidding behavior under second price auction and random nth price auction. In contrast to past studies conducted in developed countries, we generally do not see the presence of positive house money effect in our results. If behavior varies significantly as the cash endowment is varied, then care must be taken when designing auction experiments or when comparing results to other experimental results and theoretical predictions.